أثر طريقة الري في نمو محصول البندورة وإنتاجيته في البيوت المحمية. - كناج, رزان (Latakia University Journal -Biological Sciences Series, 2016)
أجريت الدراسة خلال الفترة 2014-2013 في قرية ميعار شاكر التابعة لمحافظة طرطوس بهدف تحديد طريقة الري المناسبة للحصول على أفضل نمو خضري وأعلى محصول ثمري لنبات البندورة Lycopersicon esculentum Mill.)) في البيوت البلاستيكية، باستخدام ثلاث طرق للري: خطوط (ري سطحي)، تنقيط سطحي، تنقيط تحت سطحي.أخذت القراءات الخاصة بالنمو الخضري ، والإنتاج ، والخصائص النوعية للثمار. أظهرت النتائج تفوق طريقتي الري بالتنقيط السطحي وتحت السطحي بفروق معنوية على طريقة الري بالخطوط (الشاهد ) ، من حيث: عدد الأوراق على النبات، مساحة المسطح الورقي، عدد الأزهار على النبات، إنتاج النبات الواحد الذي بلغ 4.75 ، 4.72 ، 3.95 كغ على التوالي ، ولم تكن الفروق معنوية بين طريقتي الري بالتنقيط (السطحي وتحت السطحي ).وأخذت نتائج الخصائص النوعية للثمار نفس منحى نتائج النمو الخضري والإنتاج ، إذ تفوقت معاملة الري السطحي بالتنقيط من حيث نسبة المادة الجافة ، والمواد الصلبة الذائبة الكلية ، ونسبة فيتامين c في الثمار( 28.23 ,%5.02 ,%8.28مغ فيتامين (cعلى التوالي مقارنة بطريقة الري السطحي (7.18%, 4.98%, 20.69مغ فيتامين c) على التوالي, ولم تكن الفروق معنوية بين طريقتي الري بالتنقيط (السطحي وتحت السطحي). ولم يكن أثر طريقة الري واضحاً في مؤشرات طول النبات ، ونسبة الحموضة في الثمار ، إذ كانت الفروق بين المعاملات غير معنوية. The experiment was carried out during2013-2014 Miaar Shaker village (Tartous) to determine the best method of irrigation on growth and productivity of Tomato plant in plastic green-house. Three method of irrigation were used in the experiment :(furrow surface , surface drip and subsurface drip irrigation). Growth of plants, productivity and fruit quality were studies. The results showed that surface and subsurface drip irrigation give more plant growth (leaves number and leaves area) more flowering and fruit production as compared with furrow irrigation method .The leaves number and leaves area in plant with surface drip irrigation was 31.49 leaves and 17078/plant while these number reached only to 22.91 leaves and 7057.86/plant in the furrow irrigation with significant difference . The productivity of plants was also higher in surface drip irrigation method(4.75 kg/ plant) without significant difference as compared with subsurface irrigation method and with significant difference as compared with furrow irrigation method (3.95 kg/ plant). The quality of fruits was better in surface drip irrigation (8.28% dry material ,5.02% TSS and 28.23mg vitamin c /100g) in fresh matter while these number were 7.18%, 4.98% and 20.96 mg/100g in furrow . The irrigation method haven't affect in the: plant length ,and acidity percentage